DEVELOPMENT OF HPLC STABILITY DEMONSTRATING METHODOLOGY FOR QUANTIFYING AZELNIDIPINE AND TELMISARTAN IN TABLETS AND BULK TYPES: VALIDATION FOLLOWING ICH DIRECTIVES - PONNEKANTI, KRISHNAPHANISRI; SUNITHA, K. (International Journal of Applied Pharmaceutics, 2021)
Objective: Azelnidipine (AZEL) and Telmisartan (TELM) combination is referred to the sufferers of hypertension. No analytical process has yet been mentioned for the TELM and AZEL combination analysis. We, therefore, have designed for its first time stability demonstrating methodology based on HPLC for analysing TELM and AZEL in the tablets and bulk. Methods: The assay of TELM and AZEL was get done on a 250 mm length C18 column (Supelco, 4.6 mm inner diameter, 5.0 μm particle size), and utilized 0.1M Na2SO4 (pH 3.6) and acetonitrile (55% volume: 45% volume) as the mobile solvents phase, at a stream rate 1.0 ml/min. HPLC recognition of TELM and AZEL was taken by a photodiode array sensor set at 258 nm. For validation of the stability demonstrating methodology proposed in terms of sensitivity, precision, specificity, linearity, device adequacy, robustness and accuracy, ICH directives were followed. Results: Calibration curves of TELM and AZEL were generated in the array of 20-60 µg/ml and 4-12 µg/ml with recovery percentage ranges of 99.62%-101.05% and 97.76%-100.17%, and detection limits of 0.020 µg/ml and 0.009 µg/ml, respectively. TELM and AZEL stability was inspected in the existence of acid, base, light, heat, and oxidation and it was realised to be more stable under oxidation degradation testing conditions employed when compared to acid, alkaline, photo, and heat degradation testing conditions applied. Conclusion: The observations demonstrated that the described HPLC stability demonstrating methodology was suitable for quantitating TELM and AZEL combination in tablets and bulk.